Design And Analysis Of Antenna Microstrip Patch Pi Slot Array Four Elements With Proximity Coupling Method For Multi Wide Band Characteristics: - Rudolf Mekeng; Iskandar Fitri (Institute of Computer Science (IOCS), 2021)
This research has described the design and realization of a pi-slot patch microstrip antenna array four elements who optimized by using proximity coupling method for multi wideband which is tested on frequency of 1-10 Ghz. The proximity coupling method is used to widen the bandwidth and increase the return loss value of the antenna. Based on the measurement results, it is known that the antenna designed has met the requirements of multi wide band because it has six operating frequencies with the best return loss value -30.44 dB VSWR ?2 at a frequency 5.388 Ghz with bandwidth 90 Mhz. And for the widest bandwidth 202 Mhz at a frequency 8.560-8.762 Ghz with return loss -12,19 dB VSWR ?2